COVID-19-related health literacy and preparedness to what may come: a cross-sectional study - Hebatallah Ahmed Mohamed Moustafa; Amira B. Kassem (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Since the first report of COVID-19 in 2019, information released has been fast and vast. Health literacy focuses on individual skills to obtain, process, and understand health information and services necessary to make informed health decisions. Increasing the level of health literacy can be addressed by the provision of high-quality, trustworthy, easy-to-access, and easy-to-understand information about COVID-19. This work aimed to assess COVID-19-related health literacy in the Egyptian population living in Alexandria and determine its associated factors. This cross-sectional study was performed during the second wave of the COVID-19 pandemic, using a questionnaire assessing COVID-19-related health literacy, adapted from HLS-EU-Q. The work included four phases. The first phase was questionnaire designing and tools used. The second phase included questionnaire filling by participants. The third phase was concerned with increasing population awareness about the COVID-19 pandemic. The fourth phase was the statistical analysis of the data. Results The sample compromised 3960 persons. More than half of the Egyptian population living in Alexandria have inadequate or problematic COVID-19-related health literacy scores. Female gender, younger age, higher socioeconomic status, professions with a medical background, and level of education were positively correlated with COVID-19-related health literacy. Conclusion COVID-19-related health literacy levels in the Egyptian population living in Alexandria are not sufficient. Policymakers, healthcare providers, and media must act proactively to increase the level of the citizens’ COVID-19-related health literacy and prepare them for other pandemics that may come later.